2003
DOI: 10.1053/jlts.2003.50049
|View full text |Cite
|
Sign up to set email alerts
|

Predictive models of short- and long-term survival in patients with nonbiliary cirrhosis

Abstract: The limited number of donor organs has placed a burden on the medical community to improve patient selection and timing of liver transplantation (LT). We aim to evaluate short-and long-term survival of 124 consecutive patients with a diagnosis of nonbiliary cirrhosis. Seventeen clinical, biochemical, functional, and hemodynamic parameters were computed. Patient survival was evaluated in the short term (3 months) by logistic regression, and the predictive power of the model was evaluated using receiver operatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…This could be explained by the small number of patients in our study and the probability of a type II error (beta error). Some authors have suggested that renal function parameters are better prognostic factors than liver function markers in cirrhotic patients [24,25]. Our data also revealed that the parameters of liver function did not differ between the two groups of patients and that they were not as strong prognostic factors for one-year mortality as the renal parameters turned out to be.…”
Section: Discussionsupporting
confidence: 55%
“…This could be explained by the small number of patients in our study and the probability of a type II error (beta error). Some authors have suggested that renal function parameters are better prognostic factors than liver function markers in cirrhotic patients [24,25]. Our data also revealed that the parameters of liver function did not differ between the two groups of patients and that they were not as strong prognostic factors for one-year mortality as the renal parameters turned out to be.…”
Section: Discussionsupporting
confidence: 55%
“…Interestingly, the relation was not linear and wrote as follows: INRZ (prothrombin index [% of normal]/94.9) K0.81 (unpublished data). Another group found a very similar correlation [31] suggesting that INR can be reliably estimated from prothrombin ratio for retrospective purposes. Akin to Child-Pugh score, MELD score does not (or no longer) take into account particular causes of cirrhosis and aggravating factors.…”
Section: Limitationsmentioning
confidence: 72%
“…It can be argued that studies reported thereafter, have shown that these variables do have a statistically significant impact on the outcome [3,[29][30][31][32][33]. However, not all variables have an independent influence.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one study fulfilled all quality criteria [39]. Thirty-one studies met our criteria for a 'good' quality study [32,37,39,47,55,57,60,62,63,66,76,81,85,89,92,[95][96][97]100,103,104,112,116,117,123,124,128,130,138,142,143]. …”
Section: Description Of Studiesmentioning
confidence: 99%